Education and Frankfurt school: an epistemological perspective on the critical theory of society - Guevara-Granados, Vicky I. (2021)
This article analyzes the main postulates of Max Horkheimer, main exponent of the Frankfurt School and of the critical theory of society, in order to present an epistemological perspective that compares the critical positions of the society of our times with the one conceived by the Frankfurt School. We show the qualitative results of a survey carried out on 16 professionals with a bachelor’s or master’s degree from private and national universities of Peru regarding their conceptions about Epistemology.